Preferences and perceived barriers for internet-based treatment among adolescents with anxiety or depressive disorders: A qualitative study - J. Emmelkamp; M.A. Wisman; M.H. Nauta; N.I.E. Van Rijn; J.J.M. Dekker; C. Christ (Internet Interventions, 2024)
Background: Over the past two decades, the development of internet-based treatments for adolescents with anxiety and depressive disorders has advanced rapidly. To date, adolescents' preferences and perceived barriers for internet-based treatment remain largely unknown, especially in clinical samples. Therefore, this study explored the preferences and perceived barriers of adolescents with anxiety or depression regarding internet-based treatment. Methods: This qualitative study included 21 adolescent patients with anxiety or depressive disorder, and varied levels of experience with internet-based treatment. Two focus groups (N1 = 5, N2 = 6) and semi-structured interviews (N = 10) were conducted, recorded, transcribed, and analyzed using a reflexive thematic analysis approach. Results: The thematic analysis yielded five main themes, and 12 subthemes. The main themes were: independence, accessibility, content, therapist contact, and appearance. Adolescents highlighted self-direction as a benefit of internet-based treatment, and motivational challenges as a drawback. They found internet-based interventions convenient and particularly fitting for implementation during waiting periods before formal treatment. Guided interventions were preferred over mere self-help. Furthermore, adolescents stressed the importance of a clear, organized design, and recommended accessibility on both mobile phones and computers. Conclusion: Findings provide a clear overview of the needs and preferences of adolescents with anxiety or depressive disorder regarding internet-based treatment. To address their diverse needs, internet-based interventions should be tailorable, should incorporate therapist guidance, and should already be available during the treatment waiting period. Results of this study can guide the development and implementation of new internet-based interventions, and may thereby help to further optimize their uptake among adolescent patients.